Plant-based remedies for wolf bites and rituals against wolves in the Iberian Peninsula: therapeutic opportunities and cultural values for the conservation of biocultural diversity - González, J.A. (2020)
Combined approaches to local knowledge and folk plant use improve awareness and promote effective strategies for the conservation of significant biocultural patrimony. Moreover, the information reported might be the basis for further appropriate phytochemical and pharmacological research. Therefore we provide an insight into traditional herbal remedies and practices for healing bite injuries in humans and domestic animals caused by the Iberian wolf. Wolf bites are associated with inflammatory processes and rabies is a potential complication AIMS: This paper describes and summarises the medicinal-veterinary empirical and ritual uses of the Iberian flora for wolf injuries and reviews the ethnopharmacological data of specific plants that are already published. The Iberian wolf is a critically endangered subspecies of the grey wolf. Livestock attacks attributed to wolves are increasingly frequent in the Iberian Peninsula, resulting in serious social problems. Interesting strategies for Iberian wolf conservation might be related to traditional grazing practices that are deeply linked with empirical knowledge and local practices passed on by oral tradition, which are also vulnerable now.